Writing terror on the bodies of women : media coverage of violence against women in Guatemala - England, Sarah, 1967- (Latin American gender and sexualities., 2018)
Writing Terror on the Bodies of Women: Media Coverage of Violence against Women in Guatemala analyzes the scope and dynamics of violence against women in Guatemala and how it is represented in the print media. Using nearly two thousand Guatemalan newspaper reports covering murders and assaults on women, this book contextualizes violence against women within the history of violence in Guatemala; gender ideologies and patriarchal social structures; and the contemporary demands of the women's movement for social and legislative change. It shows that while some newspapers cover violence against women with investigative reports and editorials that use feminist analysis and language, these are overshadowed by the large number of individual reports that reproduce narratives of terror and conceal the gendered nature of violence against women by suggesting that "delinquents," "gangs," "unknown men," and inexplicably violent husbands are the main culprits, while simultaneously upholding dichotomous gendered narratives of "good" and "bad" wives and daughters